An empirical study of the complexity of requirements management in construction projects. Issue 5 (9th September 2014) - Karim Jallow, Abdou; Demian, Peter; N. Baldwin, Andrew; Anumba, Chimay
Abstract : Purpose: – The purpose of this paper is to investigate in-depth the current approach of managing client requirements in construction and to highlight the significant factors, which contribute to the complexity of managing the requirements in order to define a better approach. Design/methodology/approach: – A case study of a leading international global built asset and engineering consultancy organization was conducted over two years. The case study was conducted principally using semi-participant observations supplemented with other qualitative data collection methods (i.e. interviews, questionnaires and document analysis). Thematic analysis was used to analyze the data. Findings: – The results highlight major factors associated with the complexity of managing client requirements information, which include: mechanisms for documentation, storage and access, distribution of requirements information between stakeholders and across lifecycle phases of a project, traceability management and the provision of effective change management incorporating dependency checking and impact analysis. Research limitations/implications: – The main limitation of the research is the use of an in-depth study of a single organization, which applied the same project management method across all the projects they managed. Further work is planned to develop the proposed framework fully, and develop a software platform to operationalize and evaluate its industrial applicability with construction projects. Practical implications: – The implications of this research is that a better approach to managing requirements information is needed, which will facilitate the design, construction and operations of buildings within budget and time. An integrated framework and an associated tool are suggested to implement the approach. Originality/value: – This study identifies major research gaps and problems in the architecture, engineering, construction and facilities management industry; proposes and presents Electronic Requirements Information Management framework to facilitate lifecycle management of the requirements.